Access for all: contextualising HIV treatment as prevention in Swaziland. (2nd June 2016) - Vernooij, Eva; Mehlo, Mandhla; Hardon, Anita; Reis, Ria
ABSTRACT: This article explores how notions of the individual and population are evoked in two ongoing HIV treatment as prevention (TasP) implementation studies in Swaziland. By contrasting policy discourses with lived kinship experiences of people living with HIV, we seek to understand how TasP unfolds in the Swazi context. Data collection consisted of eight focus group discussions with people living with HIV who were members of support groups to examine their perspectives about TasP. In addition, 18 key informant interviews were conducted with study team members, national-level policy-makers and NGO representatives involved in the design of health communication messages about TasP in Swaziland. Thematic analysis was used to identify recurrent themes in transcripts and field notes. Policy-makers and people living with HIV actively resisted framing HIV treatment as a prevention technology but promoted it as (earlier) access to treatment for all. TasP was not conceptualised in terms of individual or societal benefits, which are characteristic of international public health debates; rather its locally situated meanings were embedded in kinship experiences, concerns about taking responsibility for one's own health and others, local biomedical knowledge about drug resistance, and secrecy. The findings from this study suggest that more attention is needed to understand how the global discourse of TasP becomes shaped in practice in different cultural contexts.